Signs and features of law which cause the necessity of interpretation - V. K. Antoshkina (Law and Safety)
In general theory of law basic approaches to interpreting norms have been developed, but they require more attention to be paid and their improvement, especially at the current stage of development of our society in the conditions of constant updating of normative material. That is why the reasons for interpretation, including the specificities of the various spheres of law and legislation, have become the object of research in this paper.